OP01 In-depth characterisation of host genetics and gut microbiome unravels novel host–microbiome interactions in inflammatory bowel disease. (25th January 2019) - Hu, S; Vich Vila, A; Gacesa, R; Collij, V; Xavier, R; Stevens, C; Daly, M; Wijmenga, C; van Dullemen, H; Dijkstra, G; Visschedijk, M; Festen, E; et al.
Abstract: Background: A large number of host genetic factors, as well as changes in the gut microbiota, are known to determine aetiology and pathogenesis of inflammatory bowel disease (IBD). The knowledge on the interaction between these two factors is, however, still limited. To characterise these interactions, in-depth determination of the host genetics and gut microbiota is necessary. Here we aimed to identify genetic factors relevant for maintenance of the gut microbiome in the context of IBD. Methods: We performed whole-exome sequencing of the host genome, and whole-genome shotgun sequencing of faecal samples of 524 IBD patients and 939 controls from population-based cohort. The interaction between exonic variants, microbial taxa, and metabolic pathways was explored using a four-step approach: (1) Bidirectional meta-analysis between the two cohorts to identify common variants, (2) a targeted meta-analysis of IBD risk loci and protein-truncating variants (PTVs), (3) a gene-based burden test to detect rare mutations that affect microbial features, and (4) an interaction analysis to identify IBD-specific microbial quantitative trait loci (mbQTLs). Results: We tested 170000 protein-coding variants and 641 microbial features, and identified 26 associations between genetic variants and gut microbial features (FDR < 0.05). Among common variants, a strong mbQTL was observed for deletion near the IBD-risk IL17REL gene that was correlated to Alistipes indistinctus abundance, which is known to be decreased in IBD patients. The gene-based burden test revealed that mutations in an IBD-related gene CYP2D6, a major component of Phase I drug metabolism, were associated with a decreased level of bacterial biosynthesis of vitamin K (PWY-5838). Moreover, GPR151 gene, known to be protective against obesity and Type II diabetes, was found to be associated with a decrease in bacterial degradation of glucose. The interaction analysis revealed another association between BTNL2 and bacteroides specific to IBD. Conclusions: We performed the largest, high-resolution, genome–microbiome association study to date, which utilises whole-exome sequencing and metagenomics sequencing methods. Disease-specific interactions were explored in the context of IBD, including the effect of risk loci and protein-truncating variants. These results highlight the importance of host genetics in the maintenance of gut microbiome homeostasis critical for prevention of IBD.